Towards brane-antibrane inflation in type IIA: the holographic MQCD mode - Nastase, Horatiu [UNESP]; Sonnenschein, Jacob (Springer, 2012)
We describe type IIA cosmological brane inflation scenarios based on the holographic MQCD model of Aharony et al [1]. The scenarios can be related via T-duality to the type IIB KKLMMT model [2]. They describe a probe brane configuration of p D4 branes stretching between an NS5 and NS5' branes in the holographic background of large N D4 branes. The resulting cosmological models have a Wick-rotated D4-brane metric, with transverse dimensions compactified, and a spiralling brane with flux p. In one model, the background has a small nonextremality, and the inflaton is provided by the position of a "sliding" D4-brane, and in the other, the background is supersymmetric, but with a sliding anti-D4-brane. We obtain good and generic inflationary models, though several unknowns remain, in particular about subleading corrections. The usual caveat of volume stabilization generically spoiling slow-roll still applies.
Keywords: Cosmology of Theories beyond the SM; D-branes; M-Theory